2008
DOI: 10.1080/00365520801986619
|View full text |Cite
|
Sign up to set email alerts
|

Inlet patch: Associations with endoscopic findings in the upper gastrointestinal system

Abstract: Patients with inlet patch seem to have predisposing factors for gastroesophageal reflux, and Barrett's esophagus is found more frequently in those patients. H. pylori colonization is involved in ectopic gastric tissue less frequently than in gastric tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
1
20
1
4
Order By: Relevance
“…CIPs were found with a high prevalence (13.8%) in this study; however, the prevalence has been reported to be 1.0-5.1%, even in recent studies [17,[23][24][25], and generally varies from 0.1 to 10% [10]. This conflict may represent a difference in the visualization of the CIP between whitelight imaging and NBI.…”
Section: Discussioncontrasting
confidence: 52%
“…CIPs were found with a high prevalence (13.8%) in this study; however, the prevalence has been reported to be 1.0-5.1%, even in recent studies [17,[23][24][25], and generally varies from 0.1 to 10% [10]. This conflict may represent a difference in the visualization of the CIP between whitelight imaging and NBI.…”
Section: Discussioncontrasting
confidence: 52%
“…The prevalence of GIP in several large series of adults has ranged from 1.7-3.6% [22][23][24] and in the sole pediatric study it was reported to be 5.9% of 407 endoscopies. 4 The prevalence of the identification of GIP seems to be linked to the degree of awareness of the endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MUC5AC positivity was noted on the surface, pits and the glands of Barrett's esophagus. The HGMP/CIP can also be colonized by Helicobacter pylori and the patches are subjected to changes that are seen in the stomach (Akbayir et al, 2004;Alagozlu et al, 2010;BorhanManesh & Franum, 1991Gutierrez et al, 2003;Jacobs et al, 1997;Maconi et al, 2000;Poyrazoglu et al, 2009;Tang et al, 2004;Yüksel et al, 2008). Chronic inflammatory changes can be seen and progression to atrophy, intestinal metaplasia, dysplasia and malignant transformation have been reported (Borhan-Manesh & Franum, 1991).…”
Section: Histologymentioning
confidence: 99%
“…One study showed that the body or fundus mucosa type parietal cells is the most common accounting for 50 to 65% with the antral type and mixed transition type accounting for 20 to 25% respectively (Borhan-Manesh & Franum, 1991). Presence of acid producing parietal mucosa have been associated with acid production (Galan et al, 1998;Hamilton et al, 1986;Korkut et al, 2010;Yüksel et al, 2008). Mucin is also secreted (Bajbouj et al, 2009;Bogomoletz et al, 1988).…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation